The Design of a New IT Governance Framework to Optimize the Utilization of Information Technology for MSME - Yusuf, Wibisino; Yanti Rosmunie, Bujang (2022)
The presence of industry 4.0 brings various conveniences in opera-tional and marketing processes for companies, including micro, small and me-dium enterprises (MSMEs). All companies are required to be able to utilize in-formation technology in order to win the competition. Based on 2019 data, the number of MSMEs in Indonesia is 99.99% of the total number of companies and contributes to a GDP of 61.1%. With a large number of MSMEs in Indone-sia, their existence also opens up wider job opportunities with more equitable economic benefits for the community. To win the competition, MSMEs must optimize the use of information technology. To use information technology to align with business goals, MSMEs need IT Governance. Implementation of the IT Governance Framework generally runs in large companies. Constraints for small companies are usually related to the cost and complexity of the existing IT Governance Framework. This paper aims to develop an IT Governance Framework suitable for MSMEs and can be applied easily and efficiently. The initial stage is to develop a framework based on a literature review of the exist-ing frameworks, namely COBIT, ITIL, CMMI, TOGAF, and relevant research. The proposed framework consists of six main components: Architectural Read-iness, Technology Adoption, Service Management, Continuous Improvement, Leader Engagement, and Network Capability. Subsequently, improvements were made to the proposed framework by conducting quantitative and qualita-tive research on MSMEs to produce a better framework. As a validation stage, the enhanced framework will then be discussed with experts and the response from the MSMEs. Thus, it is hoped that the proposed framework can help MSMEs effectively utilize information technology that supports and is in line with MSME's business values.